Investigation on effect of pulse frequency on nanostructure and electrocatalytic active surface area of platinum pulse electroplated on niobium. (1st July 2013) - Nasiri Vatan, H; Jafarzadeh, K; Mirjani, M
Abstract : The electrocatalytic active surface area is an important parameter in platinum anodes. In this research, the effect of frequency, a pulse electroplating parameter, on the nanostructure of platinum plated on niobium has been studied. The experiments were performed in a Q salt solution, based on platinum tetraammine, at a duty cycle of 30%, at an electrolyte temperature of 93°C, pH = 10·5, and in a frequency range of 2·5 to 90 Hz. The electrocatalytic active surface area of the coatings was estimated by cyclic voltammetry and the nanostructure of the coatings was studied by scanning electron microscopy and atomic force microscopy. The results showed that the highest electrocatalytic active surface area is obtained at an optimum frequency of 15 Hz. The cone shaped nanostructure of the coating at this frequency is such that the area is 10% more than the typical semi spherical platinum coating, whereas at other frequencies, the surface becomes monotonous and smooth.